Histopathologic findings and assessment of cervical lymph node metastasis in oral squamous cell carcinoma of Malaysian patients - Ismail, S.B.; Zain, R.B.; Kipli, N.P.; Abraham, T.; Ismail, M.S.; Rahman, Z.A.A.; Prepageran, N.; Jalaludin, M.A.B. (Wiley, 2006)
Purpose: To evaluate some histopathologic parameters and relate with the occurrence of cervical lymph node metastasis in oral squamous cell carcinoma (OSCC) in Malaysian patients. Methods: A total of 44 cases of OSCC resected were included. The resected specimens were examined for the OSCC type, degree of differentiation, pattern of invasion (at the tumour invasive front), greatest dimension and the depth of stromal invasion. Where there is no neck resection, the clinical nodal status was obtained from the Oral Cancer database maintained at the University of Malaya Oral Cancer Research and Coordinating Centre (UM-OCRCC) while the histopathologic data were obtained from examination of the resected specimens of patients whose records were extracted from the UM-OCRCC. Results: Among 38 cases of conventional OSCC, 11 cases showed nodal metastasis (28.9 %); two out of 4 cases of basaloid SCC showed nodal metastasis (50%) and none of the papillary SCC (2 cases) showed nodal metastasis (0%). The occurrence of lymph nodes metastasis in well-differentiated, moderately-differentiated and poorly-differentiated OSCC are 17.6% (17 cases), 36.0% (25 cases) and 50.0% (2 cases) respectively. None of the cases with pattern of invasion Type 1 and 2 (cohesive) showed nodal metastasis. The occurrence of lymph node metastasis in tumours with Type 3 and 4 pattern of invasion (non-cohesive) are 34.5% and 42.9% respectively. Ten out of 23 cases (43.5%) with depth of stromal invasion of ?1.0cm showed nodal metastasis while three out of 21 cases (14.3%) of those with < 1.0 cm depth showed nodal metastasis. Eleven out of 29 cases (37.9%) with tumour greatest dimension of ?2.0 cm showed nodal metastasis and two out of 15 cases (13.3%) with nodal metastasis was observed among those patients with < 2.0 cm greatest dimension. Conclusion: The pattern of invasion, depth of stromal invasion and tumour?s greatest dimension appear to be important parameters in the occurrence of cervical lymph node metastasis for the Malaysian OSCC patients.